Prognostic indicators of subacute combined degeneration from B12 deficiency: A systematic review. Issue 4 (19th May 2021) - Jhunjhnuwala, Dhruv; Tanglay, Onur; Briggs, Nancy E.; Yuen, Margaret T. Y.; Huynh, William
Abstract: Objective: A systematic review was conducted on published data of subacute combined degeneration (SCD) from B12 deficiency to investigate potential prognostic indicators of final ambulatory function in affected patients. Type: Systematic review. Literature Survey: Records published from 1999 through 2018 were searched on the electronic databases MEDLINE, PUBMED, and SCOPUS. The publication language was restricted to English and French. Methodology: Records that described cases of SCD from B12 deficiency in patients ≥16 years of age at onset were included. From a final total of 66 cases of SCD identified, ambulation scores were assigned based on the clinical descriptions reported. Patient characteristics, clinical manifestations, and ambulatory function were reported descriptively. Subanalyses on potential prognostic indicators were performed. Synthesis: Greater ambulatory function at diagnosis was associated with recovery of normal ambulatory function at follow‐up ( P  <  .001). Nearly 90% of patients walking unsupported at diagnosis made a complete recovery regardless of etiology. For patients initially walking with support, 22% of cases from impaired B12 digestion/absorption made a complete recovery compared with ≥50% of cases from other etiologies. For patients initially requiring a wheelchair, 33% of cases from impaired digestion/absorption were able to walk with support compared with ≥50% of cases from other etiologies. The total B12 administered over the course of treatment was correlated with improved ambulation ( P  = .024 ) for all patients, with a higher B12 replacement regimen associated with better outcomes in patients who were unable to walk unsupported at diagnosis (number needed to treat = 4). Conclusions: Initial ambulatory function may be a useful clinical marker of the severity of spinal cord dysfunction and final functional outcome. Etiological risk factors influenced both clinical manifestations and final walking ability in SCD, suggesting a distinct pathophysiological mechanism among the causes. In addition, a more intensive B12 replacement regimen may improve ultimate ambulatory function in advanced cases of SCD.